(untitled) (Physical Education, Health and Social Sciences, 2025)
Background: Diabetes mellitus (DM), particularly type 2 diabetes (T2DM), is a growing global health concern, with over 537 million adults affected worldwide as of 2021. T2DM is associated with a range of complications, including cardiovascular disease, nephropathy, and neuropathy. An often overlooked but significant complication is anemia, which can worsen outcomes in diabetic patients. Anemia in T2DM is multifactorial—commonly linked to chronic inflammation, reduced erythropoietin production due to diabetic nephropathy, and nutritional deficiencies. Pro inflammatory cytokines like IL-6 and TNF-α play a central role by suppressing erythropoiesis and increasing hepcidin levels, which impairs iron metabolism. Anemia is common in diabetic patients and is linked to higher cardiovascular risk, faster kidney disease progression, lower quality of life, and increased mortality. Despite its impact, it often goes undiagnosed, especially in low-resource settings. This study aims to assess the frequency of anemia in diabetics versus healthy individuals and emphasize the need for routine anemia screening in diabetes care. Methods: A comparative cross-sectional study was conducted at a community care center (Sehar Medical Center Karachi. Data were collected from 150 participants, both diabetic patients and healthy individuals. Hemoglobin (Hb) levels were used to identify anemia, and self-structured questionnaire were used to assessed knowledge, anemia status, life style and diabetes mellitus stouts. Result: High prevalence of diabetes and anemia was observed, with 63.6% and 41.6% mean affirmative responses, respectively. Significant associations were found between disease duration and complications in diabetes (p < 0.01), and between hemoglobin testing and anemia diagnosis (p < 0.001). Lifestyle factors like diet and sleep significantly predicted better hemoglobin levels. Conclusion: The findings highlight the burden of chronic conditions and underscore the importance of regular screening, symptom monitoring, and lifestyle interventions. Strengthening education and early detection efforts is essential for improving health outcomes.